Employment polarization in Germany: Role of technology, trade and human capital - Davide Consoli; Ipsita Roy (Friedrich Schiller University Jena, 2015)
Building on the canonical model of skill-biased technical change to incorporate differential effects of technology and international trade on the skill composition of occupations, the paper employs a task-based approach to analyze structural changes in regional employment within a rich vocational education setting in West Germany during 1979 and 2012. Results confirm theoretical predictions that regional employment districts with high initial share of routine occupations have experienced greater subsequent adoption of computer and information technology and larger decline in routine occupations. Exposure to global imports in goods and services have reduced overall employment in routine-intensive occupations; the magnitude being notably smaller as compared to technology. However, when looking at the direction of displacement of routine-workers, regions with greater share of routine jobs have experienced greater growth of high-skilled abstract jobs in the subsequent periods while the overlap between initial apprenticeship intensity and subsequent decline in regional routine employment is significantly strong. Taken together, findings show that unlike in the U.S. where employment growth in low-skilled service occupations has been the greatest, in Germany there is a greater trend towards occupational upgrading and larger growth in managerial and professional occupations due to the operationalization of its apprenticeship system.
Keywords: E24; F16; J21; J24; O33; R23; 330; apprenticeship; international trade; regional employment districts; skill-biased technical change; skill composition; task-based approach; technology